2007
DOI: 10.3354/meps333271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grazing by Canada geese Branta canadensis on an intertidal eelgrass Zostera marina meadow

Abstract: Fishing Island, in Portsmouth Harbor on the Maine-New Hampshire border (USA), is the site of an intertidal eelgrass (Zostera marina L.) bed that is part of SeagrassNet, an international program for long-term seagrass monitoring. Eelgrass bed parameters of canopy height, percent cover, and aboveground biomass have been monitored quarterly since October 2001 using the SeagrassNet protocol. A flock of nearly 100 Canada geese Branta canadensis L. over-wintered at Fishing Island and grazed on eelgrass from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…During the first year of SeagrassNet monitoring (October 2001 through July 2002), data for the eelgrass parameters of percent cover, canopy height, and aboveground biomass showed the typical seasonal changes of eelgrass abundance at Fishing Island (Rivers & Short 2006). Eelgrass canopy height and aboveground biomass showed similar seasonal fluctuations at all three cross transects, with low values occurring in January and peak values occurring in July; percent cover and shoot density data followed a similar trend (Fig.…”
Section: Results and Discussion: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first year of SeagrassNet monitoring (October 2001 through July 2002), data for the eelgrass parameters of percent cover, canopy height, and aboveground biomass showed the typical seasonal changes of eelgrass abundance at Fishing Island (Rivers & Short 2006). Eelgrass canopy height and aboveground biomass showed similar seasonal fluctuations at all three cross transects, with low values occurring in January and peak values occurring in July; percent cover and shoot density data followed a similar trend (Fig.…”
Section: Results and Discussion: Case Studiesmentioning
confidence: 99%
“…In conclusion, monitoring showed that 96% of the seagrass (eelgrass, Zostera marina L.) at the SeagrassNet monitoring site in New Hampshire (USA) was lost in the first quarter of 2003, a consequence of intensive grazing by Canada geese, Branta canadensis L. (Rivers & Short 2006), birds which historically migrated south during the winter. With a warmer climate, these birds now reside in New Hampshire throughout the year, increasing the grazing pressure on seagrasses.…”
Section: Results and Discussion: Case Studiesmentioning
confidence: 99%
“…Several other large herbivore species occasionally consume submerged angiosperms, including other cervids, mainly based on availability and comprising only a minor fraction of their diets, as far as data are available. Sources: data on habitat, diet and range for mammals from MacDonald (2001) Table 2); it is not uncommon for turtles and swans to consume ca 100% of primary production in a given season (Rivers and Short 2007, Hidding et al 2009, Kelkar et al 2013a, Christianen et al 2014. A lot of the variation in herbivory rates observed among studies is likely due to variation in herbivore densities (Wood et al 2012a).…”
Section: Dietsmentioning
confidence: 99%
“…Several other studies have documented that grazing by herbivorous waterbirds affect the submerged vegetation in terms of leaf length, and below ground biomass (Bortolus et al, 1998), and above ground biomass (Rivers and Short, 2007;Dos Santos et al, 2015) but temporal removal of plant material does not necessarily have a permanent impact on the plants. Some aquatic plants such as Potamogeton pectinatus are in fact extremely "tolerant" to intense and annual grazing by swans, and may overcompensate and thus produce better in the presence of grazing (Nolet, 2004).…”
Section: Grazing and Fluctuations In Eelgrass Populationsmentioning
confidence: 99%